Simulation of the Energy Performance of a Building with Green Roofs and Green Walls in a Tropical Climate - Pragati, Saranathan; Shanthi Priya, Radhakrishnan; Pradeepa, Chandramouli; Senthil, Ramalingam (Sustainability, 2023)
Global temperatures have continued to rise for decades, partly due to human-caused greenhouse gas emissions and subsequent urban heat island (UHI) effects. This current research examines the benefits of urban greenery by studying the impact of green roofs and walls of a building on thermal behavior and heat transfer in a warm and humid climate. This simulation study discusses the importance of greening systems in improving thermal comfort and minimizing the causes of UHI by assessing an integrated green building design. Using the simulation software DesignBuilder, the significance of greening systems, green roofs, and walls in enhancing thermal comfort and reducing the factors that contribute to UHI is investigated. The simulation results are based on the building’s energy usage in hot and humid regions while featuring green roofs and walls. The simulation results indicate a considerable positive impact of greening systems in improving the urban environment in hot and humid tropical climates. Air temperature, radiant temperature, humidity, and solar gain are decreased by urban greening. The total energy consumption and district cooling demand of buildings with green roofs and walls are reduced by 10.5% and 13%, respectively. The greening systems substantially improve air quality and building’s energy efficiency. Thus, the present study‘s findings can benefit urban designers and dwellers in devising strategies for establishing green spaces in congested urban environments by integrating green technologies and systems into built environments.